Neutralising antibodies after streptokinase treatment for myocardial infarction: a persisting puzzle. Issue 2 (August 1995) - McGrath, K.; Hogan, C.; Hunt, D.; O'Malley, C.; Green, N.; Dauer, R.; Dalli, A.
Abstract : OBJECTIVE–To determine the development of titres of streptokinase (SK) neutralising antibodies after a single dose of SK, to establish when titres decrease to levels at which a second dose might be effective. DESIGN–Analyses of blood samples taken from patients at intervals after SK administration. SETTING–Australian public hospital. PATIENTS–104 patients with acute myocardial infarction who were treated with SK and 27 controls who were not. OUTCOME MEASURE–SK neutralising antibodies were measured once in each of the 27 controls and on 166 occasions in the 104 treated patients. RESULTS–Titres of SK neutralising antibodies rose after SK administration but returned to control levels by 2 years. CONCLUSIONS–SK might be effective again as a thrombolytic agent as early as 2 years after a single dose. These results are at variance with most previously published data and the reasons for this are not clear. Data evaluating patency rates after standard doses of streptokinase in patients with increased titres of neutralising antibodies are necessary before re-exposure to streptokinase can be recommended.